Impact of the hydraulic loading rate on the hydrodynamic characteristics of an anaerobic fixed bed reactor treating cattle slaughterhouse wastewater - Kreutz, Cristiane (2018)
The hydrodynamic behavior of an anaerobic fixed bed reactor (AFBR) was evaluated in the treatment of cattle slaughterhouse wastewater. The AFBR was operated at hydraulic retention time (HRT) of 14, 11 and 8 h. Stimulus-response assays were carried out with Eosin Y and the experimental data were adjusted to the single-parameter theoretical models of dispersion and N-continuous stirred tank reactors in series (N-CSTR). The experimental results of the residence time distribution curves showed that at lower flow rate, the reactor showed plug flow behavior with correlation coefficient (r) of 0.88 and number of dispersion of 0.2 for high dispersion (HD). However, at higher and intermediate flow rates, the AFBR behave as a complete mixture flow, (r) of 0.94 and 0.96, respectively. Residence time distribution curves in the AFBR showed a good approximation of the complete mixing model at hydraulic residence time of 11 and 8 h, with 5 and 2 N-CSTR reactors in series, respectively. The volume of dead zones corresponding to 43.0, 37.4 and 11.2% of the volume of the reactor for HRT of 14, 11 and 8 h, respectively, was noted, and hydraulic short circuiting were not confirmed